Evaluation of Metabolizable Energy and Protein of Rice Bran on Mojosari laying Ducks - Asnawi Asnawi; Dwi Kusuma Purnamasari; I Ketut Gde Wiryawan (Faculty of Animal Husbandry, University of Mataram, 2020)
Evaluation of metabolizable energy of local rice bran have been conducted on Mojosari laying duck. The purpose of study was to calculate the energy values of local rice bran. Ten Mojosari laying ducks were randomly allocated of two types of feeds. Each laying duck was reared in individual cage (metabolic cage). Two types of feeds were basal diet (30% commercial feed: 70% corn), and 70% basal diet and 30% local rice bran. There are five duck as replication in each types of feed. Metabolic energy (ME) was determined according to Farrel (1978) with any modification. The results indicated that the gross energy and apparent metabolically energy (AME) of rice bran were approximately 3317,00±17,30 kkal/kg and 2461,44±27,76 kkal/kg. Presentation of AME to Gross energy of local rice bran were 74.21 %. Metabolizable protein of local rice bran were 55,71 ± 9,30% from crude protein intake. It is concluded that according to apparent metabolically energy (AME) and digestible protein, local rice bran is appropriate as supplement feed of laying duct particularly Mojosari laying ducks.